LEGAL REASONING OF THE JUDGE'S DECISION REGARDING GOVERNMENT PROCUREMENT CONTRACT GUARANTEE CLAIM - A Malik, Djamil; Erwin, Yulias; Nurjannah Septyanun (Awang Long Law Review, 2023)
The decision is a written legal text made by an authorized judge, and its legal product is categorized as a crown. However, despite being considered a crown, a judge's decision is not exempt from examination by legal scholars. The optics used in the examination process are based on various perspectives, including hermeneutics as the fundamental basis for interpreting the text (decision). Substantively, hermeneutics has three main streams of thought, namely as a theoretical (methodological), philosophical, and critical hermeneutics, each with different understandings. Hermeneutics as a method focuses more on the effort to capture and reveal the meaning of the text, while philosophical hermeneutics goes beyond that and emphasizes "capturing meaningful meaning," implying that the meaning of the text can be continuously produced through a dialectical process. On the other hand, critical hermeneutics focuses on the aspect of disclosing the meaning of the author's ideological interests. This research aims to examine the legal reasoning in Decision No. 272 / PDT.G / 2017 / PN.BDG regarding the Government Procurement Contract Guarantee Claim from the perspective of Hans Georg Gadamer's Hermeneutic Circle. The research type is normative doctrinal, using secondary data sources consisting of primary, secondary, and tertiary legal materials with a conceptual approach, statutory approach, and case study. The research findings suggest that the process of claiming a bank guarantee through the judicial institution can be carried out by the Procurement Committee (PPK) as long as they obtain authorization from the Budget User, who is the owner of the work (bouwheer). This is due to the hybrid nature of government procurement contracts, which distinguishes them from private contracts, and the clarity of the scope of authority of the Budget User serves as the establishment of formal justice, acting as a bridge (epistemology) toward substantive justice.